Evaluating stakeholders' willingness to pay for an improved and collaborative fisheries management in selected coastal communities of Leyte Gulf, Eastern Visayas Philippines - Amigo, Miriam F.; Parilla, Richard B. (Tacloban City Division of Natural Sciences and Mathematics, University of the Philippines Tacloban College, 2025)
This study examines the willingness of the stakeholders to pay for an enhanced Monitoring, Control, and Surveillance (MCS) design to improve fisheries management, primarily in coastal communities in Guruan, Giporlos, and Balangiga in Eastern Samar and Tanauan, Tolosa, and Dulag in Leyte. A fish catch survey, household survey, and key informant interviews (KII) were conducted to assess fisheries' resources, stakeholder awareness, and willingness to contribute financially to MCS improvements. The fish catch survey documented a total of 129 species across 45 families. Sailfish (Istiophoridae) represented the highest proportion of the catch at 14.15%, followed by scads (Carangidae, 13.95%), threadfin breams (Nemipteridae, 12.28%), slipmouths or ponyfishes (Leiognathidae, 7.57%), and mackerel (Scombridae, 6.22%). Together, these and 14 other families comprised 91% of the total recorded catch. Additionally, ten types of fishing gear were identified, with the most prevalent being hook and lines and other line methods (n57, 40%), followed by gillnets (n50, 35%), traps (n27, 19%), seine nets (n=3, 2%), and longlines (n= 1. 1%). Local management strategies commonly featured gear restrictions, marine protected areas, coastal resource plans, fisherfolk registration, and community empowerment. Each LGU implemented these differently, shaped by their unique contexts and the influence of NGOs, national agencies, and academic institutions Stakeholders' knowledge and perceptions were generally low across technical and social dimensions (11%-29%), MCS activities (11% 52%), and overall awareness of MCS systems (11%-42%), resulting in a neutral composite perception score (mean = 3.36) Despite this, 49% of respondents indicated a willingness to contribute financially to services aimed at strengthening local fisheries management, reflecting moderate support for cost-sharing in implementation. Using the Turnbull method, the estimated average annual willingness to pay across the six municipalities was calculated as Follows. Php 143.50 for Balangiga, Php 137.20 for Guiuan, Php 50.66 for Giporlos, Php 51.78 for Tanauan, Php 478.07 for Tolosa, and Php 66.39 for Dulag. These amounts are proposed to be collected annually through licensing or registration fees. Results from the binary logistic regression analysis indicated that in the Eastern Samar municipalities, key determinants of willingness to pay included knowledge of MCS concepts, awareness of MCS importance, and understanding of MCS application at the municipal level. In contrast, for the municipalities in Leyte, significant predictors were the gender of the household head, gross monthly income, perceptions of fisheries management activities, and knowledge of existing MCS practices.
Master's thesis (Master of Science in Environmental Science) -- University of the Philippines, Tacloban.
Keywords: Fishery management -- Economic aspects -- Philippines -- Eastern Visayas; Fish catch monitoring; MCS; KAPP survey; Willingness to pay